"Lengyelország és Magyarország a nyugati civilizáció két bástyája” : Hóman Bálint lengyelországi látogatása (1935 ősz) = ”Poland and Hungary, two bastions of Western civilization" : Bálint Hóman's visit to Poland (fall of 1935) - Debreceni, Péter (Közép-Európai Közlemények, 2017)
Bálint Hóman, arrived in Warsaw on the 3 November 1935 for practical implementation of Intellectual Cooperation Agreement concluded on the 21 October 1934. The Hungarian Minister spent seven days in Poland: in the capital, as well as Vilnius and Cracow. During his stay he visited many educational and cultural institutions (besides the three major universities in these cities), opened the Hungarian Institute in Warsaw, met the Polish President, the Prime Minister and also the representatives of local Hungarian expat groups. Throughout his visit he felt the amazing sympathy and great friendship of his hosts and – despite the state of their internal diffi culties – every detail of his visit was carefully planned. The events was followed by the Polish press (as well as the Hungarian one) very attentively, Homan was also granted an honorary doctorate. The practical results of inter-state cooperation had tangible eff ects already in 1936. Apart from the opening of the Hungarian Institute, people formed their own Hungrian friendly associations, in the coming years there were many mutually organized art and literature programme too. The number of Polish students attending the Summer University of Debrecen had for example defi nitely increased up until the outbreak of World War II.